Role of oral dehydroepiandrosterone in diminished ovarian function - Dayal, Meena; Chaurasia, Amrita; Singh, Urvashi; Gupta, Veena; Patel, Shweta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Ovarian reserve decreases with age and this study determine the effect of oral DHEA supplementation on S.AMH concentration and conception rate in women with diminished ovarian function. Methods: The study was conducted on 72 infertile women of 20-45 years age who had S.AMH <2.2 ng/ml, which was taken as cut off for diminished ovarian reserve in the study. The cases of study group received oral DHEA 25mg TDS and cases of control group received placebo (folic acid 5 mg OD) for 12 weeks. Day 2 S.AMH, S.FSH, S.LH, S.E2, S. Inhibin B, ovarian volume and AFC were measured at first visit and after 12 weeks of oral DHEA or placebo. Results: After 12 weeks of oral DHEA supplementation, S. AMH concentration was found to be significantly improved (p=0.01). S.FSH was decreased (p=0.04) and S. E2 was increased (p=0.03). S. LH showed insignificant decrease. S. Inhibin B, ovarian volume and AFC were increased but insignificantly. Improvement in ovarian reserve resulted in significantly higher pregnancy rate (p=0.04) and live births (p=0.04) in women treated with DHEA than in the control group. Miscarriage rate was found to be decreased but insignificantly. Conclusions: DHEA improves the ovarian reserve.